Strange Bedfellows at Work: Neomaternalism in the Making of Sex Discrimination Law - Deborah Dinner (Washington University Law Review, 2014)
In contests about pregnancy discrimination during the 1970s, feminists, the business lobby, and anti-abortion activists disputed the meaning of sex equality. Existing scholarship has yet to take account of the dynamic interaction between these groups. This Article fills that void by analyzing the legal and political debates that resulted in the passage of the Pregnancy Discrimination Act of 1978 (“PDA”). The Article reveals how competing ideas about the family, wage work, and reproductive choice shaped the evolution of pregnancy discrimination law. Feminists, the business lobby, and anti-abortion activists drew upon two legal discourses in debating pregnancy discrimination: liberal individualism and “neomaternalism.” Each of these discourses, in turn, encompassed dual valences. Liberal individualist discourse challenged sex-role stereotypes, but it also reinforced the idea that private reproductive choice rendered reproduction a private economic responsibility. Neomaternalism leveraged the social value of motherhood to gain entitlements for pregnant women, but also reinforced the normative primacy of motherhood. Feminists’ legal goals and rhetorical frames at times overlapped with and at other times diverged from those of both the business lobby and anti-abortion activists. Feminists used liberal individualist principles of equal treatment and neutrality to challenge gender stereotypes that states and employers used to justify the exclusion of pregnancy from public and private insurance schemes. The business lobby used liberal individualist principles of private choice to advance a market libertarian interpretation of sex equality that justified the denial of pregnancy-related benefits. In opposition to the business lobby, both feminists and anti-abortion activists forged a fragile alliance. Both groups made neomaternal arguments in advocating the PDA. While feminists emphasized the value of pregnancy as a form of socially productive labor, however, anti-abortion activists stressed the need to protect pregnant women and fetuses. The points of confluence and departure between the arguments of feminists, business opponents, and anti-abortion allies both advanced sex equality under the law and also limited its scope. Feminist advocates for the PDA synthesized liberal individualist and neomaternal discourses to pursue the elimination of sex-role stereotypes under the law as well as collective societal responsibility for the costs of reproduction. While the PDA took a significant step toward the realization of this vision, it remains illusory. Our legal culture evolved to embrace not only the valences of liberal individualist and maternalist ideologies that advance sex equality but also those valences that reinforce gender inequality. Market libertarianism continues to privatize the costs of reproduction, while maternalism reinforces the sexual division of reproductive labor. Ultimately, this Article points to the persistence of tensions in the definition of sex equality and the consequent need for new legal paradigms.
Keywords: employment; sex; discrimination; Pregnancy Discrimination Act; PDA